Peran Financial Controller dalam Pengelolaan Keuangan Perusahaan - Harefa, Christine Cahyanti; Lubis, Imelda Fisianca; Sihite, Ingot M.; Siagian, Natalia P. M.; Sipayung, Rizki Christian (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
In an increasingly complex and dynamic business environment, corporate financial management has become a crucial factor in maintaining business stability and sustainability. One of the key roles in this aspect is the Financial Controller, who is responsible for financial planning, oversight, and reporting to ensure the efficiency and effectiveness of corporate operations. This study aims to analyze the role of the Financial Controller in corporate financial management and identify the factors that support the effectiveness of this role in improving corporate financial performance. This research employs the Systematic Literature Review (SLR) method to examine the role of the Financial Controller in financial management. SLR is a structured approach to collecting, critically analyzing, integrating, and synthesizing findings from various studies related to a specific topic or research question. The findings indicate that the role of the Financial Controller is essential in corporate financial management. Controllers are responsible for preparing and analyzing financial reports that serve as the foundation for managerial decision-making, ensuring compliance with corporate policies, and monitoring financial transactions. Additionally, they oversee the accurate recording of accounts receivable, inventory, and sales prices to ensure alignment with established policies.